2015
DOI: 10.3109/00365521.2015.1017834
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality among patients with compensated and decompensated liver cirrhosis: the role of bacterial infections and infection-related acute-on-chronic liver failure

Abstract: In a population-based cirrhotic cohort, infection-related ACLF was a negative predictor of survival in decompensated disease. Infection-related ACLF was frequent and related to cirrhosis severity and infection acquisition type, as well as to high inpatient mortality, in particular in patients with significant comorbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 32 publications
3
25
0
1
Order By: Relevance
“…In fact, Asian Pacific Association for the Study of the Liver only considers variceal bleeding a precipitant if it results in liver failure, whereas the European Association for the Study of the Liver and the American Association for the Study of Liver Diseases consider it as a precipitant in all cases . Either way, it is suspected that acute variceal bleeding precipitates ACLF mainly due to hepatic ischemia, increased bacterial translocation from the gut, and subsequent bacterial infections . The prevalence of variceal bleeding as the precipitant of ACLF ranges from 13% to 28% of patients depending on the study .…”
Section: Gi Hemorrhagementioning
confidence: 99%
“…In fact, Asian Pacific Association for the Study of the Liver only considers variceal bleeding a precipitant if it results in liver failure, whereas the European Association for the Study of the Liver and the American Association for the Study of Liver Diseases consider it as a precipitant in all cases . Either way, it is suspected that acute variceal bleeding precipitates ACLF mainly due to hepatic ischemia, increased bacterial translocation from the gut, and subsequent bacterial infections . The prevalence of variceal bleeding as the precipitant of ACLF ranges from 13% to 28% of patients depending on the study .…”
Section: Gi Hemorrhagementioning
confidence: 99%
“…17 Other 2 studies suggest that nosocomial infections are independent predictors of ACLF. 18,19 Type and severity of infections were partially described in these studies with no mention on other characteristics of bacterial infections, microbiology and relationship with clinical course.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the presence of DC independently increases mortality rates for other gastrointestinal diseases, including diverticulitis, peptic ulcer disease, Clostridium difficle infections, [25][26][27] along with non-gastrointestinal bacterial infections. 28 This appears to be the case for ABP as well. Additional risk factors for mortality during index hospitalization include increasing age, sepsis, and SAP, all of which are known risk factors for mortality in acute pancreatitis, with an augmented effect in cirrhosis patients.…”
Section: Discussionmentioning
confidence: 83%